Assessment of risk factors for upper extremity musculoskeletal disorders by OCRA index in Meybod potters in 2009 - H Fallah; R Khani Jazani; A Barkhordari; MA Lahmi; GH Halvani; M Movahedi (طب کار)
Background: Work-related musculoskeletal disorders are the most common occupational diseases. Between industries, pottery, with several thousand years of activity, still retains its nature as a manual job. This has led to increased risk of musculoskeletal disorders among potters. The aim of this study was to assess the prevalence of musculoskeletal disorders and related risk factors by OCRA method in Meybod potters in 2009. Methods: This was a cross-sectional analytical study. Target population consisted of, all potters working in the pottery workshops in Meybod. There were 17 workshops with 54 potters. Information about the prevalence of musculoskeletal disorders was collected using Nordic questionnaire. The OCRA method was used to assess risk factors for musculoskeletal disorders of upper limbs. Results: The results of Nordic questionnaire showed that approximately 59.3% of the potters had at least one upper extremity musculoskeletal disorders in the last year. Wheel workers had the highest prevalence (34.4%). Independent T-test showed no significant difference between the final score of OCRA index between potters with and without upper extremity musculoskeletal disorders (P=0.047). Conclusion: The results of this study showed that the risk of musculoskeletal disorders of upper extremities is high among potters. So it suggested that possible corrective actions take place as soon as possible and periodic evaluations are also necessary for early detection of these disorders.